An empirical definition of the role of education in business - A. A. Buimov; A. V. Glotko (Вестник университета)
Currently, the development of small and medium businesses is considered a key driver for the formation and growth of market economy, which is especially true for Russia, since the contribution of these types of businesses to gross domestic product is low. However, in the Russian Federation there are still no in-depth studies of the factors of entrepreneurial activity development, one of which is the level of education. This paper examines the impact of education, especially economic education, on success in entrepreneurship. The authors analysed data on Russian billionaires and found that one in three of them has a degree and only 3 % do not have a higher education, which is very different from the national average. Then, with the help of the counterparty reviewing service, an inspect of teachers from the Novosibirsk State University of Economics and Management (thereinafter referred to as NSUEM) was made on doing business, which showed the connection between the level of education, turnover and business net profit. The main result of the study is a sociological survey of the NSUEM teaching staff about doing business. It made possible to formulate a number of conclusions on the degree and nature of the influence of the education level on entrepreneurship. In particular, a comparison was conducted: assessments of the main factors hindering business progress, according to ordinary entrepreneurs from the survey provided by Synergy University, were compared to the answers of entrepreneurs of the current study.